RANCANG BANGUN SISTEM INFORMASI PENDUDUK DUSUN (STUDI KASUS : DUSUN TEGAL KORI KAJA UBUNG) - I Gede Iwan Sudipa; Eka Ayu Purnama Lestari (Jurnal Teknologi Informasi dan Komputer, 2019)
ABSTRACTThe population data processing system is very important for all population administration processes in a village, or in a smaller scope, namely hamlets. An information system is needed to access population data, so that one can use it to carry out population track records and simplify the process of population registration. Tegal Kori Kaja Hamlet is located in Ubung Kaja Village, North Denpasar District. Currently village officials carry out data collection on paper and processing population data by storing data in word and excel documents, making it difficult and slowing down the process of reporting and archiving population data including data on KK (Head of Family), Population Data, Arrivals Data, Data on Death, Birth Data and Transfer Data. With these problems, a population data information system will be designed which can help village government organization officials, especially hamlet heads in recording and managing population data, so they can produce population report and can provide information on population status to all people because this system based on website and can be accessed by all people .Keywords: system, information, populationABSTRAKSistem pengolahan data penduduk sangat penting bagi segala proses administrasi kependudukan dalam suatu desa, ataupun dalam ruang lingkup yang lebih kecil yaitu dusun. Suatu sistem informasi diperlukan untuk mengakses data kependudukan, sehingga diantaranya dapat digunakan untuk melakukan rekam jejak penduduk serta mempermudah dalam proses pendataan penduduk. Dusun Tegal Kori Kaja terletak pada desa Ubung kaja kecamatan Denpasar Utara. Saat ini aparat desa melakukan pendataan penduduk dengan kertas dan pengolahan data penduduk yang dilakukan dengan menyimpan data-data dalam dokumen word dan excel, sehingga menyulitkan dan memperlambat proses pelaporan dan pengarsipan data penduduk meliputi data KK (Kepala Keluarga), Data Penduduk, Data Pendatang, Data Kematian, Data Kelahiran dan Data Perpindahan. Dengan permasalahan tersebut maka akan dirancang sistem informasi data penduduk dusun yang dapat membantu pemerintahan desa, khususnya kepala dusun dalam pencatatan dan pengelolaan data penduduk sehingga dapat menghasilkan laporan penduduk dan dapat memberikan informasi status kependudukan kepada seluruh penduduk karena sistem informasi berbasis website dan bisa diakses oleh seluruh masyarakat.Kata Kunci : sistem, informasi, penduduk